Robert Lehmann-Nitsche y Rudolf Lenz: Epistolario (1897-1928) - Ennis, Juan Antonio; Soltmann, Claudio (Variaciones, 2022)
This book offers a transcription, translation and annotation of the correspondence between the German scholars Rudolf Lenz and Robert Lehmann-Nitsche, based in Chile and Argentina respectively.